AB1222 Subclinical atherosclerosis and oxidized LDL levels in familial mediterranean fever. (23rd January 2014) - Ugurlu, S.; Karaca, S.N.; Demirel, Y.; Seyahi, E.
Abstract : Background: To investigate markers of carotid atherosclerosis and oxidized low density lipoprotein(oxLDL) levels in patients with Familial Mediterranean Fever (FMF) who have no risk factors for cardiovascular disease. Methods: We studied 44 patients (25 F/19 M; mean age: 33.5±7.5)with FMF in attack free period and gender and age matched 44 healthy subjects (25 F/19 M; mean age: 33.4±7.0). Exclusion criteria were clinical coronary artery disease, chronic renal disease, diabetes mellitus, hypertension, history of myocardial infarction, angina pectoris or cerebrovascular disease, dyslipidemia, metabolic syndrome or active infection. Those who were in postmenopausal status and using anti-lipid drugs were also excluded. We measured carotid artery intima- media thickness (IMT) and investigated presence or absence of atherosclerotic plaques in the carotids, using Doppler ultrasound. We also assessed serum lipid and OxLDL levels. Results: Mean disease duration of the FMF patients was 20±9 years. The mean carotid IMT (C-IMT) did not differ between patients and controls (0.52±0.10 mm vs 0.53±0.06 mm, respectively, P=0.709). None of the patients or controls had atherosclerotic plaques. Total and LDL cholesterol levels were significantly lower among patients compared to controls (total cholesterol: 157.07±34.18 vs 181.05±36.79, respectively, P=0.002; LDL cholesterol: 100.48±30.13 vs 126.25±34.05, respectively, P=0.001). Whereas OxLDL levels were significantly higher in FMF patients (337.48±438.56 ng/dl) when compared to controls (156.19±383.24 ng/dl), (P=0.044). There was no correlation between CIMT and OxLDL levels among both patients (r= -0.156, p=0.324) and controls (r=-0.196, p=0.246). Conclusions: Our study supports further evidence for no increased atherosclerosis in FMF. As previously shown patients with FMF have low cholesterol levels when compared to healthy controls [1, 2]. On the other hand, increased OxLDL levels could be associated with increased sub-clinic inflammation. References: Ugurlu S, Seyahi E, Cetinkaya F, Ozbakir F, Balci H, Ozdogan H. Intima-media thickening in patients with familial Mediterranean fever. Rheumatology (Oxford). 2009;48:911-5. Akdogan A, Calguneri M, Yavuz B, et al. Are familial Mediterranean fever (FMF) patients at increased risk for atherosclerosis? Impaired endothelial function and increased intima media thickness are found in FMF. J Am Coll Cardiol 2006;48:2351-3. Disclosure of Interest: None Declared